A MODERN VIEW ON THE PHENOMENOLOGY OF SOCIAL-PSYCHOLOGICAL ADAPTATION AND MALADAPTATION - Nasriddinova Shakhnoza Musurmon qizi (Bright Mind Publishing, 2025)
Changes are taking place at a rapid pace in modern society. Technological progress, social networks, globalization and economic changes have a great impact on the lives of young people. It is important to study how these changes affect the social adjustment of young people and how they adapt to new conditions.
Keywords: Modern world, society, globalization, problems, skills, norms, values.